Pause toward Nassie Judge’ Speech on Nassie Judge’ Youtube - Dewi Kartika Nurtaspeni; Agus Wismanto; Siti Ulfiyani (Universitas PGRI Semarang, 2023)
Pause is one of the speech impediments that anyone can experience. This study aims to determine the forms of pause and the reasons that cause pause in Nessie Judge's speech. The data used is in the form of Nessie Judge's utterances which contain pauses. The approach used in this research is descriptive qualitative. The methods used to collect data are documentation techniques, observation methods, and note-taking techniques. The data obtained were then analyzed using the matching and distribution method. Based on the data analysis carried out, the results are in the form of two forms of pause, namely silent pause and filled pause. The reasons that caused Nessie Judge to experience pause, namely forgetting, attracting attention, looking for the right words, giving time to understand the utterances, taking a breath, already starting the utterances, and being careful when speaking.